2011
DOI: 10.1248/bpb.34.671
|View full text |Cite
|
Sign up to set email alerts
|

Nateglinide Stimulates Glucagon-Like Peptide-1 Release by Human Intestinal L Cells via a KATP Channel-Independent Mechanism

Abstract: The incretin effect is markedly reduced in patients with type 2 diabetes, mainly due to defective glucagon-like peptide-1 (GLP-1) secretion from the intestinal L cells in response to stimulation by various nutrients. 1,2) This leads to impairment of early-phase insulin secretion after food intake and consequently results in postprandial hyperglycemia and hyperlipidemia. [3][4][5][6] GLP-1 is an incretin hormone that is released by intestinal L cells following their stimulation by nutrients, 7,8) and it promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
1
15
1
Order By: Relevance
“…In the present study, nateglinide significantly increased the AUC of glucagon during the meal test compared with sitagliptin. In contrast, regarding the effect on GLP‐1 in vitro , nateglinide increases the plasma GLP‐1 level by inhibition of DPP‐4 activity and direct stimulation of GLP‐1 release from L‐cells. However, in the present study, this difference could be related to the study condition.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In the present study, nateglinide significantly increased the AUC of glucagon during the meal test compared with sitagliptin. In contrast, regarding the effect on GLP‐1 in vitro , nateglinide increases the plasma GLP‐1 level by inhibition of DPP‐4 activity and direct stimulation of GLP‐1 release from L‐cells. However, in the present study, this difference could be related to the study condition.…”
Section: Discussioncontrasting
confidence: 76%
“…However, in the present study, this difference could be related to the study condition. In fact, the use of nateglinide at a dose higher than the clinical dose was reported to have a direct effect on L‐cells to enhance GLP‐1 release. Taking these previous studies into consideration, the inhibitory effect of DPP‐4 activity and the stimulatory effect of GLP‐1 after the administration of a clinical dose of nateglinide might be very modest.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, 21 GLP-1 release from NCI-H716 cells was stimulated by glucose in a dose-dependent manner (Fig. 4, control, n ϭ 10 each).…”
Section: Effects Of Isoflurane On Glp-1 Secretion From Nci-h716 Cellssupporting
confidence: 86%
“…The rationale for combination therapy was based on previous preclinical studies that evaluated the effect of meglitinide on DPP-4 activity. In these studies, it was demonstrated that meglitinide (nateglinide) prevents DPP-4-mediated GLP-1 degradation in both a time-and concentration-dependent manner [26,27]. However, a glucose-lowering effect of combination therapy in this study was not better than mitiglinide monotherapy, although it was better than sitagliptin monotherapy.…”
Section: Discussionmentioning
confidence: 51%